Slenderness in Steel Fibre Reinforced Concrete Long Beams - Ravpreet Kaur; Harvinder Singh (Salehan Institute of Higher Education, 2022)
Slenderness influences in steel fibre reinforced concrete (SFRC) long beams are not adequately addressed in current concrete design regulations. The present guidelines are confined to semi-empirical formulations for limiting slenderness ratio, but largely restricted to RC beams. Many scholars have already examined RC long beams and successfully presented the slenderness ratio formula for RC long beams. This article proposes a novel term for limiting the slenderness ratio for SFRC long rectangular beams based on the fundamental principle of mechanics and taking into account the slenderness impact of RC long beams as well as the flexural moment capacity of SFRC beams. The suggested formulation for limiting slenderness ratio agrees closely with experimental data and may reliably forecast the mode of collapse. The proposed limiting slenderness ratio formulation takes into consideration beam end circumstances, loading conditions, concrete strengths, steel, tension and compression reinforcement ratios, and transverse reinforcement ratios, among other factors. It is revealed that a wide variety of slenderness limits may be achieved for varied sets of design parameters. The researchers' predictions and the suggested equation are compared to the test results of 9 SFRC beams. The suggested equation fits well with the results of the tests that have been done so far. Doi: 10.28991/CEJ-2022-08-06-011 Full Text: PDF